Perceptions of health and healthcare needs in low-resource settings: qualitative insights from Bengaluru's urban slum and rural areas - Dubbala, Keerthi; Spahl, Wanda; George, Carolin Elizabeth; de Witte, Luc (Frontiers in Public Health, 2025)
BackgroundDespite the multitude of healthcare services available in India, health inequalities persist. People in low-resource settings are both disadvantaged and have the greatest need for healthcare. To address these disparities and achieve universal health coverage, healthcare services need to be tailored to the specific needs of this population.ObjectiveThis study aimed to understand health and healthcare perceptions of people in slums and villages in and around Bengaluru, a city in the southern part of India. It was conducted in partnership with Bangalore Baptist Hospital, a charity hospital dedicated to supporting underserved populations in this region.MethodsThe study employed qualitative methods. Twenty-eight open-ended interviews and eight focus groups were conducted with residents of selected slums and villages in and around Bengaluru. The interviews were transcribed verbatim, translated to English and analyzed applying thematic analysis.Results and conclusionThe study finds that participants defined health as the absence of illness, the ability to work, and the result of a good lifestyle. With regards to healthcare expectations, the analysis shows the themes of the “good doctor,” recovering quickly, cost affordability, cleanliness, and emergency services and diagnostic facilities. In addition, stigma related to healthcare, was identified, especially among residents of villages. Participants highlight the importance of good relationships with healthcare providers and accessible healthcare facilities to improve healthcare uptake in Bengaluru's slums and rural areas. This study also shows that achieving universal health coverage requires addressing not only direct costs but also other associated expenses like travel and lost wages, considering healthcare costs as a comprehensive expense tied to patients' living conditions. These results contribute to the growing body of literature on health and healthcare perceptions in low-resource settings, offering insights that may inform future research and context-specific strategies for improving healthcare access and delivery.